FORMULATION AND EVALUATION OF MINOXIDIL GEL USING ACRYLAMIDE/SODIUM ACRYLOYLDIMETHYL TAURATE COPOLYMER FOR ALOPECIA AREATA (International Journal of Pharmaceutical Sciences and Drug Research, 2018)
Alopecia areata is a common, chronic inflammatory disease, characterized by patchy hair loss on the scalp, affecting about 2.1% of world population. Presently, minoxidil has been used for treatment of alopecia as topical lotion, but associated with many drawbacks like systemic side effects and low contact time with skin. Therefore, in the present work, minoxidil gel was prepared using a novel copolymer, Sepineo P 600 to overcome these drawbacks. The prepared gel was characterized for pH, drug content, viscosity, spreadability, skin adhesivity, occlusivity, in vitro drug release, ex vivo skin permeation, stability and finally for skin corrosivity. The drug content of the finalized gel was found to be 99.80 ± 0.82%. The formulation showed good spreadability, occlusivity, adhesiveness and viscosity. In vitro release studies showed that the drug release from prepared gel followed matrix release pattern as compared to lotion. Mathematical modelling of the drug release data suggested Higuchi release model. The formulated minoxidil gel was found to be non-corrosive and stable when subjected to accelerate as well as real time stability studies. Overall, the minoxidil gel formulation was suitable for skin application and can be an effective dosage form for the treatment of Alopecia areata.